2008
DOI: 10.1089/met.2007.0025
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in Railway Employees and its Relation to Lifestyle Factors

Abstract: These results from a representative sample of Solapur division railway employees show that the MeTs is highly prevalent mainly in sedentary workers aged 45 years or older. The large numbers of Indian Railway employees with the MeTs may carry important implications for the health care sector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…This finding agrees with the results of the study conducted by Mangat et al [17] who documented that using IDF, the prevalence of MS was more prevalent among females (59.6%) than males (40.4%). Similar results were reported in studies conducted by Pemminati et al ,[18] Sidorenkov,[23] Kamble et al ,[15] Parale et al [24] and Gupta et al [16] whose results showed a higher prevalence of MS in females than males.…”
Section: Discussionsupporting
confidence: 90%
“…This finding agrees with the results of the study conducted by Mangat et al [17] who documented that using IDF, the prevalence of MS was more prevalent among females (59.6%) than males (40.4%). Similar results were reported in studies conducted by Pemminati et al ,[18] Sidorenkov,[23] Kamble et al ,[15] Parale et al [24] and Gupta et al [16] whose results showed a higher prevalence of MS in females than males.…”
Section: Discussionsupporting
confidence: 90%
“…(1214) To date only a handful of studies have been conducted in order to assess the impact of one's occupation in development of MS.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that there is a significant prevalence of diabetes and MS in the urban Indian population with the prevalence being age related and more so among the sedentary workers. ( 12 14 ) To date only a handful of studies have been conducted in order to assess the impact of one's occupation in development of MS.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been done on Indian population to identify the positive association between cardiovascular disease and many metric variables 2010a;2010b;Gupta et al, 2007;Parale et al, 2008;Badaruddoza and Sawhney, 2009;Shah and Mathur, 2010). The results of present study indicated that SBP and DBP have positive association with waist-to-hip ratio, body mass index, waist circumference, skin folds, pulse pressure, HDL and triglycerides.…”
Section: Discussionmentioning
confidence: 99%